Correct Solvability of the Cauchy Problem for One Equation of Integral Form - Litovchenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We describe spaces of test functions that generalize S-type and W-type spaces. In these spaces, we establish the complete solvability of the Cauchy problem for one equation of integral form with Bessel fractional integro-differential operator.